Menggali Potensi Calon Guru Penggerak Melalui Kegiatan Lokakarya - Wijaya, Herman; Ernawati, Titin; Nahdi, Khirjan; H. Gani, Ramlah; Supratmi, Nunung (Universitas Negeri Gorontalo, 2023)
The Assistance of candidate Teacher Mover is a forum for developing the competence of leader learning in driving the educational ecosystem, encouraging learning innovation, and strengthening teacher commitment and motivation. The workshop activity aims to identify and explore the potential of candidate teacher mover through Junior High School (SMPN) 1 Selong workshop activities. The devotional method is evaluation and collaboration between practical teacher and candidate teacher mover. The assistance results showed that the workshop activities at SMPN 1 Selong effectively explored the potential of teacher mover. During these activities, the candidate teacher mover is challenged to work in groups, lead discussions, and manage projects individually so that this activity develops leadership skills, teamwork, creativity, and problem-solving. In addition, through these workshop activities, students also better-understood education and the role of a teacher. They can observe how teachers facilitate the learning process, face a problem in teaching, and interact with students. Through this activity, the candidate teacher mover can develop leadership skills and practical knowledge needed in the teacher profession. Hopefully, this approach can be widely applied in other schools to support improving the quality of education in the digital era.